2019
DOI: 10.20945/2359-3997000000172
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of TGFβ signaling and microRNA in thyroid cell loss of differentiation and cancer progression

Abstract: Thyroid cancer has been rapidly increasing in prevalence among humans in last 2 decades and is the most prevalent endocrine malignancy. Overall, thyroid-cancer patients have good rates of long-term survival, but a small percentage present poor outcome. Thyroid cancer aggressiveness is essentially related with thyroid follicular cell loss of differentiation and metastasis. The discovery of oncogenes that drive thyroid cancer (such as RET, RAS, and BRAF), and are aligned in the MAPK/ERK pathway has led to a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Further, metastasis-related cytokines were positively regulated by UHRF1. According to our previous and present results in thyroid cancer, UHRF1 should be an essential gene in dedi erentiation and metastasis [7,[26][27][28]. roughout cancer development, the main published downstream targets of UHRF1 were tumor suppressor genes.…”
Section: Discussionsupporting
confidence: 54%
“…Further, metastasis-related cytokines were positively regulated by UHRF1. According to our previous and present results in thyroid cancer, UHRF1 should be an essential gene in dedi erentiation and metastasis [7,[26][27][28]. roughout cancer development, the main published downstream targets of UHRF1 were tumor suppressor genes.…”
Section: Discussionsupporting
confidence: 54%
“…As elucidated by Fuziwara and cols. in a recent review, a series of different microRNAs can target mRNA related with the TGF-β1 signaling pathway, and its deregulation is frequently seen in thyroid neoplasia (43).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exploring the pathological mechanism of thyroid cancer is of great clinical significance for the diagnosis and treatment of patients with thyroid cancer. miRNAs are non-coding microRNAs, which mainly influence the biological function of cells through mRNA matching with downstream target genes (5). Studies have shown that miRNAs play a vital part in the occurrence and development of thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%